Increasing the discovery and use of NonPatent Literature (NPL): scientific publications in patent examination - Loizides, Fernando; Diallo, Barrou; Pollard, Andrew; Mavri, Aekaterini (My University, 2017)
In this work we present findings on non-patent literature use, and specifically scientific publications such as academic articles. We interview patent examiners and observe their prior art searching in order to provide insights into the perceived usage of non-patent literature and produce high level requirements for advancing non-patent literature search tools.
Keywords: Patents; Patent examination; Non-patent literature; NPL; Scientific literature; Academic publications; Intellectual property